STRICTs: A Blockchain-enabled Smart Emission Cap Restrictive and Carbon Permit Trading System. (1st May 2022) - Lu, Youshui; Li, Yue; Tang, Xiaojun; Cai, Bowei; Wang, Hua; Liu, Lei; Wan, Shaohua; Yu, Keping
Abstract: As the first legally binding global agreement on climate change, the Paris Agreement aims to limit long-term global warming to less than 2 °C, preferably below 1.5 °C compared to pre-industrial levels. Road transport, as one of the primary sources of energy consumption and carbon emissions, has great potential for energy conservation and emission reduction in achieving the climate goals. However, current approaches cannot efficiently reduce road travel, making it challenging to decarbonize in the transport sector. Therefore, in this paper, we propose STRICTs, a blockchain-enabled motor vehicle restrictive and trading system based on the carbon emissions cap. STRICTs allows automated carbon emission auditing and carbon emission violation punishment without relying on third-party escrow. Through a decentralized enforcer, STRICTs also enables carbon permit trading reliably and transparently. Finally, we implement a proof-of-concept prototype of the system based on Hyperledger Fabric and conduct experiments for comprehensive performance evaluation through CO2 Emission by Vehicles dataset . The experiment results show the practically affordable performance of STRICTs. Graphical abstract: Highlights: Carbon emission calculation and carbon emission permit allocation method is developed. Vehicle data chain is built to guarantee the reliability and correctness of collected vehicle data. Restrictions on carbon emission allowance is presented to reduce carbon emissions. A smart-contract-based decentralized enforcer is proposed to audit user's carbon emission behavior.